Identification of Decision-Making Skills of the High School Students Participating in School Sports Activities - Ayla Karakullukçu; Mehmet Öçalan; Pelin Avcı (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to identify the decision-making skills of the high school students participating in school sports activities. The sample of the study consisted of 221 (n=96 girls and n=125 boys) volunteer students studying in 4 different high schools affiliated to Kırıkkale Provincial Directorate of National Education in 2017-2018 academic year. The students participating in the study were divided into 3 different age groups. 49.3% (n=109) of the students are in the 14-15 age group, 35.7% (n=79) are in the 16-17 age group and 14.9% (n= 33) are in the 18-19 age group. "Melbourne Decision-Making Questionnaire" which was developed by Mann, Burnett, Radford and Ford (16) and whose validity and reliability in Turkish were carried out by Deniz (9) was used in the identification of decision-making skills of the students. The data obtained from the questionnaire were evaluated in SPSS 22.0 package program at 95% confidence interval and 0.05 significance level. In this study, the effect of two or more independent variables on more than one dependent variable was determined by two-way MANOVA analysis. In the statistical analyses, it was found that there was no interaction between the dependent variables (F(15, 577,36)=.86, p gt;0.05) and there was a statistically significant difference between the self-confidence, which is one of the sub-dimensions of the decision-making, and grade variable (F(3,213)=2.85, p lt;.05). In addition, it was determined that there was a statistically significant difference between the self confidence and team or individual sport variable (F(1,213)=7.18, p lt;.05). According to the findings obtained from the study, it was concluded that the highest mean value obtained from the decision-making styles of the students who participated in the school sports activities belonged to Part I “self-confidence", and also the self-confidence of the 12th grade students was higher than the 9th grade students. Another result obtained from the study is that the students who are interested in team sports have higher self-confidence than the students who are interested in individual sports. As a result of the evaluation, the fact that the students participating in the study adopted the style "Self-Esteem (Self-Confidence) in Decision-Making" at the most supports the hypothesis of this study.